Barriers-enablers-ownership approach: a mixed methods analysis of a social intervention to improve surgical antibiotic prescribing in hospitals. Issue 5 (10th May 2021) - Broom, Jennifer; Broom, Alex; Anstey, Chris; Kenny, Katherine; Young, Sharon; Grieve, David; Sowden, David; Jangam, Aishwarya; Henderson, Andrew; Melon, Alexandra; Tabone, Renee; Farquhar, Drew; et al.
Abstract : Objectives: To assess an intervention for surgical antibiotic prophylaxis (SAP) improvement within surgical teams focused on addressing barriers and fostering enablers and ownership of guideline compliance. Design: The Queensland Surgical Antibiotic Prophylaxis (QSAP) study was a multicentre, mixed methods study designed to address barriers and enablers to SAP compliance and facilitate engagement in self-directed audit/feedback and assess the efficacy of the intervention in improving compliance with SAP guidelines. The implementation was assessed using a 24-month interrupted time series design coupled with a qualitative evaluation. Setting: The study was undertaken at three hospitals (one regional, two metropolitan) in Australia. Participants: SAP-prescribing decisions for 1757 patients undergoing general surgical procedures from three health services were included. Six bimonthly time points, pre-implementation and post implementation of the intervention, were measured. Qualitative interviews were performed with 29 clinical team members. SAP improvements varied across site and time periods. Intervention: QSAP embedded ownership of quality improvement in SAP within surgical teams and used known social influences to address barriers to and enablers of optimal SAP prescribing. Results: The site that reported senior surgeon engagement showed steady and consistent improvement in prescribing over 24 months (prestudy and poststudy). Multiple factors, including resource issues, influenced engagement and sites/time points where these were present had no improvement in guideline compliance. Conclusions: The barriers-enablers-ownership model shows promise in its ability to facilitate prescribing improvements and could be expanded into other areas of antimicrobial stewardship. Senior ownership was a predictor of success (or failure) of the intervention across sites and time periods. The key role of senior leaders in change leadership indicates the critical need to engage other specialties in the stewardship agenda. The influence of contextual factors in limiting engagement clearly identifies issues of resource distributions/inequalities within health systems as limiting antimicrobial optimisation potential.